Petani dan Pedagang: Perubahan Ekonomi dan Agama di Buton - Blair Palmer (Antropologi Indonesia, 2011)
This article examines a dispute over proper religious practice in an all-Muslim village in Buton, Southeast Sulawesi. Traditionalists and modernists disagree over whether agricultural ceremonies involving offerings for territorial spirits should be allowed to continue. Local views on this dispute are explored with reference to the historical context of religious practice in the village, and processes of social change over the past several generations. It is argued that key social, political and economic dynamics which are relevant to the current religious dispute include the decline of agriculture in the village, the eclipsing of the Butonese Sultanate and integration into the Indonesian state, and new patterns of mobility whereby many villagers have become migrants to urban centers in eastern Indonesia. Thus it traces how processes of the increasing penetration of capitalism, the decline of traditional authority, and new patterns of mobility have played out in this particular village in the context of a dispute over religious practice. Key words: Islam, trade, Buton, Indonesia, agriculture, religion, migration